Seagrass mapping in Cyprus area of interest with pixel-based classification - Makri, Despina; Melillos, George; Kalogirou, Eleftheria; Hadjimitsis, Diofantos G. (My University, 2023)
Seagrasses are one of the most valuable ecosystems in the sea. Seagrasses provide shelter and protection to newborn fish, and food, it is an indicator of the health of coastal ecosystems and plays a key role in the protection of erosion. Seagrasses provide many ecosystem services. In order to act helpfully for the health of this kind of valuable ecosystem, it is very important to map the seagrass beds. Seagrass mapping allows us to detect, monitor, and finally protect them from different sources of pressure. Seagrasses are very sensitive to changes, and this can affect the health of this type of ecosystem. For the first step, we have to detect what exists in Cyprus's area of interest. There are many ways we can implement the detection and mapping of seagrass. We will provide an estimation with pixel-based image analysis. The purpose of the paper proceedings is to detect seagrass with pixel-based image analysis, in Cyprus's area of interest, and especially the broader area of Paphos district.
Keywords: Pixel-based classification; Seagrass; Sentinel-2